Pengaruh Kualitas Produk,Penetapan Harga,Dan Strategi Promosi Terhadap Keputusan Pembelian Mobil Bekas Honda Pada Arengka Auto Mall Pekanbaru - Saidudatun Nadya; Mashur Fadli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Purchasing decisions are an important part of the product marketing concept and this is the background of this research. Product quality, pricing, and promotion strategy are part of the factors supporting consumer purchasing decisions. This study aims to determine the effect of product quality, pricing and promotion strategy on purchasing decisions of used Honda cars at Arengka Auto Mall Pekanbaru. The method in this study was carried out through a questionnaire method given to consumers, and interviews with the owner of Arengka Auto Mall Pekanbaru. The population in this study amounted to 82 respondents who were obtained using the Accidental Sampling technique. The analytical method uses descriptive and quantitative analysis. Data analysis testing uses validity and reliability tests. Data analysis test and hypothesis testing using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results of the study revealed that product quality (X1), pricing (X2), promotion strategy (X3) had a significant effect on purchasing decisions (Y) for used Honda cars at Arengka Auto Mall Pekanbaru. Keywords: product quality, pricing, promotion strategy, purchasing decision